Crosstalk between transforming growth factor-β signaling pathway and long non-coding RNAs in cancer. Issue 2 (28th January 2016) - Wang, Jianbo; Shao, Na; Ding, Xiaowen; Tan, Bingxu; Song, Qingxu; Wang, Nana; Jia, Yibin; Ling, Hongbo; Cheng, Yufeng
Highlights: Tumor-suppressing or tumor-promoting effect of TGF-β signaling pathway in tumorigenesis. LncRNAs regulating the canonical or non-canonical members of TGF-β pathway. Vast majority of lncRNAs reported to be induced by TGF-β signaling pathway. The clinical significance of lncRNAs involved in TGF-β signaling pathway in human cancers. Therapeutic potential of lncRNAs involved in TGF-β signaling pathway in cancer. Abstract: The transforming growth factor-β (TGF-β) signaling pathway plays an important role in tumorigenesis by exerting either a tumor-suppressing or tumor-promoting effect. Long non-coding RNAs (lncRNAs), a newly discovered class of non-coding RNAs, have been widely studied in recent years and identified as crucial regulators of various biological processes, including cell cycle progression, chromatin remodeling, gene transcription, and posttranscriptional processing. Recent evidence, addressing the crosstalk between the TGF-β signaling pathway and lncRNAs in cancer, found that several members of the TGF-β pathway are targeted by lncRNAs, and the production of hundreds of lncRNAs is induced by TGF-β treatment. This review will summarize the latest progress on the investigation of TGF-β pathway and lncRNA network in regulating cancer development. Further study on the network would provide a better understanding of carcinogenesis and have potentials for the prevention and treatment of malignant diseases.